Impact assessment of coastal marine range shifts to support proactive management. Issue 3 (16th December 2021) - Henry, Amy K; Sorte, Cascade J B
Abstract : Climate change is reshuffling Earth's biota as species shift their current ranges to track suitable conditions, often in response to increasing habitat temperatures. While redistribution may be necessary for species persistence, there can also be impacts on existing communities upon arrival of novel, range‐shifting species. Anticipating the beneficial versus deleterious impacts of range‐shifting species is essential for determining whether active management is needed, which could include implementation of strategies from facilitation (eg managed relocation) to suppression (eg prevention and control). We used an impact assessment protocol developed for invasive species to evaluate potential consequences of range shifts in coastal marine ecosystems of North America. Our review demonstrates how invasion impact assessment combined with species vulnerability assessment could support decisions about management of range shifts. We found that ~50% of these shifting coastal species have had negative impacts in their expanded ranges. The importance of proactive management is likely to increase as the number and extent of range shifts accelerates.